Korpus Hadis Bertema Persia - Faisal Amri Al-Azhari (Yayasan Bayt Shufiya Nusantara, 2025)
This study examines the virtues of the Persian nation as reflected in the Hadiths of the Prophet Muhammad (peace be upon him). The Persians are assumed to be a great nation and are even categorized under the term ‘umrān kullī (imperium) in Ibn Khaldun’s theory. The focus of this research is to trace textual evidence that highlights the virtues of the Persians.The study employs a library research method with a descriptive-analytical approach, gathering data from Quranic verses, authoritative Hadith collections, and other relevant references that support the research. The analysis is carried out through data enrichment, presentation, and conclusion-drawing regarding the virtues of the Persian people mentioned in the Prophet’s Hadiths. The findings indicate that Persia was a major empire in its time, possessing a sophisticated civilization encompassing religion, governance, authority, and territorial control. Furthermore, many influential Persian figures played significant roles in Islam ic history. Several Quranic verses’ occasions of revelation (asbāb al-nuzūl), contexts of Hadith narration (asbāb al-wurūd), and even certain Islam ic legal rulings are linked to Persia.